Association between alopecia areata and thyroid dysfunction. Issue 8 (17th November 2021) - Naik, Piyu Parth; Farrukh, Syed Nadir
ABSTRACT: Alopecia Areata is an inflammatory and T cell-mediated autoimmune reaction against unknown autoantigen of hair follicles characterized by patchy, non-scarring loss of hair follicles in the anagen phase. Although its etiology is minimally understood, genetic susceptibility, autoimmunity and stress are thought to be causative factors. It occurs in episodic and recurrent patterns with an incidence rate of 0.1–0.2% in the general population and 7–30 cases per 1000 dermatological patients with a lifetime risk of 1.7%. The lesions can be single and self-limiting or may be widespread. Autoimmune disorders such as Hashimoto's thyroiditis, Vitiligo, celiac disease, diabetes mellitus, psoriasis ad lupus erythematosus were observed as an associated comorbid disorder in AA patients, but hypothyroidism and Vitiligo have the strongest association. Its clinical course is unpredictable and shows no significant predilection to age, gender or race. AA is a heterogeneous variant of alopecia and has clinical types such as patchy alopecia, alopecia reticularis and alopecia totalis. Various epidemiological reports demonstrate an increased frequency of AA in thyroid disease patients. Contemporary research has shed spotlight on circulating auto-reactive cells in evolution of AA, which may play a role in ultimately linking these diseases. Comprehension of complex interplay between autoantigens and immune cells is still evolving. The present study will explore this association of Alopecia Areata in patients with thyroid dysfunction. This correlation was studied briefly with literature available in the medical database such as PubMed and Google Scholar.